No place to hide: Marine habitat does not determine per- and polyfluoroalkyl substances (PFAS) in odontocetes - Stockin KA; Peters KJ; Saltré F; Machovsky-Capuska GE; Betty EL; Tremblay LA; Yi S (Elsevier B.V., 2025)
As meso- and apex predators in food webs, marine mammals can bioconcentrate persistent environmental contaminants like per- and polyfluoroalkyl substances (PFAS). Although the presence of PFAS is widely reported in the marine environment, there is a lack of data for cetaceans in Oceania. We investigated whether ecological habitat influences bioconcentration patterns across a range of odontocete (toothed whale, dolphin and porpoise) species. We measured PFAS in liver samples (n = 127) from 16 cetacean species representing four families inhabiting four marine habitats along the Aotearoa New Zealand coastline. We analysed six perfluoroalkyl carboxylic acids, ten perfluoroalkyl sulphonic acids and four precursor compounds in the context of sex, body index, habitat and species/family using generalized linear mixed models. Results showed that marine habitat remained a weak predictor of PFAS burden. Instead, biological factors including sex and age class best explained the levels of PFAS detected across all species and habitats. We offer first important insights on PFAS levels across several new taxa globally, including endemic endangered species and poorly described polar vagrants. Our findings further highlight how the ubiquitous nature of PFAS pose a higher risk to odontocetes across different seascapes than previously anticipated.
Keywords: Emerging contaminants; Bioaccumulation; Seascape; Cetaceans; Life history; New Zealand